Collision of Two Cultures in East is East by Ayub Khan-Din - Makrlíková, Lucie (Univerzita Pardubice, 2012)
The main subject of this paper is the analysis of the play East is East by Ayub Khan-Din. In the initial part of this work, the history of Commonwealth immigration, racism and the second generation of immigrants and their assimilation to Britain are contextualized and the specifics topics of the aforementioned play are pointed out. In the following part, the actual play is analysed. The analysis focuses on the elements of the generation gap and the clash of two cultures. Then, it is mentioned how these problematic parts of the life influenced the second generation children of immigrants.
Střetnutí dvou kultur v dramatickém díle East is East od Ayub Khan-Din
Keywords: East is East; generační rozdíly; střety dvou kultur; imigranti; rodina Khanových; generation gap; clashs of the cultures; immigrants; Khan family